Corporate tax avoidance and stock price crash risk: The moderating role of audit quality - Luu , Ngoc Bao; Le , Hieu Ngan; Mai , Tran Phuong Nghi; Truong, Phuong (Journal of Finance - Marketing Research, 2026)
Drawing on agency theory, this study aims to examine the moderating effect of audit quality on the relationship between corporate tax avoidance and stock price crash risk. Using panel data of 140 firms listed on HOSE and HNX from 2017 to 2024, and addressing endogeneity issues through GMM, the results reveal that audit quality shows a significant moderating effect on the relationship between corporate tax avoidance and stock price crash risk. These results highlight that tax avoidance provides an opportunity for managers to conceal bad information, which may accumulate and trigger stock price collapses, while audit quality mitigates such concealment behavior by the managers, promotes more transparent information disclosure and thereby reduces the stock price crash risk. The study contributes to the literature by showing evidence of these relationships from an emerging market and highlights important implications. Investors should incorporate tax avoidance indicators and also the audit quality of corporates into risk assessments, while policymakers are encouraged to strengthen tax enforcement, enhance disclosure requirements and promote improvements in external audit firms to enhance stock price market transparency and stability.